VP49 Brazilian Consumer Willingness To Pay For Dengue Vaccine (CYD-TDV). (12th January 2018) - Godói, Isabella; Santos, André; Reis, Edna; de Lemos, Livia Pires; Brandão, Cristina; Alvares, Juliana; Acurcio, Francisco; Bennie, Marion; Godman, Brian; Guerra, Augusto
Abstract : INTRODUCTION: Dengue virus is a serious global health problem with an estimated 3.97 billion people at risk for infection worldwide. In December 2015, the first vaccine (CYD-TDV) for dengue prevention was approved in Brazil, developed by Sanofi Pasteur (1). However, given that the vaccine will potentially be paid via the public health system, information is needed regarding consumers willingness to pay for the dengue vaccine in the country, as well as discussions related to the possible inclusion of this vaccine into the public health system at prices suggested by the manufacturer. This was the objective of this research. METHODS: We conducted a cross-sectional study with residents of Greater Belo Horizonte, Minas Gerais, about their willingness to pay for the CYD-TDV vaccine. Respondents had to be over 18 years and not currently have the disease although they may have had dengue in the past (2, 3). RESULTS: Five-hundred and seven individuals were interviewed, who were mostly female (62.4 percent), had completed high school (62.2 percent), were working (74.4 percent), had private health insurance (64.5 percent) and did not have dengue (67.4 percent). The maximum median value of consumers willingness to pay for the CYD-TDV vaccine, assuming vaccine efficacy against virologically-confirmed symptomatic dengue illness of approximately 60 percent, is USD33.61 (BRL120.00) for the complete 3-course schedule and USD11.20 (BRL40.00) per dose. At the price currently being assessed by the Brazil's regulatory chamber of pharmaceutical products market (CMED) for Dengvaxia® for three doses, only 17 percent of the population expressed a willingness to pay for the vaccine at this price. CONCLUSIONS: Brazil is currently one of the largest markets for dengue vaccine in the world and the price established is a key issue. The manufacturer should asses the possibility of lowering its price in Brazil to reach a larger audience among the Brazilian population, especially as other public health activities to control the disease will continue.